GeoComputation - Abrahart, Robert J., 1956-; See, Linda, 1966- (CRC Press, 2014)
"This newly updated edition covers cutting-edge topics in computational geography, addressing a domain in both geographic and computer sciences. With an extended introduction that reviews directional changes and major advances in the field since the first edition, this book includes ten new topics as well as substantial modifications to existing chapters. Written by recognized international experts and up-and-coming researchers, the text introduces the subject matter by providing readable accounts of current developments. In addition, the authors examine possibilities for future developments through the year 2061"-- Provided by publisher.
Keywords: Information storage and retrieval systems -- Geography.; Geographic information systems.; elektronické knihy; electronic books